Triple A syndrome (Allgrove syndrome): improving outcomes with a multidisciplinary approach - Flokas ME; Tomani M; Agdere L; Brown B (Dove Medical Press, 2019)
Myrto Eleni Flokas, Michael Tomani, Levon Agdere, Brande BrownDepartment of Pediatrics, NewYork-Presbyterian Brooklyn Methodist Hospital, Brooklyn, NY, USACorrespondence: Brande BrownDepartment of Pediatrics, NewYork-Presbyterian Brooklyn Methodist Hospital, 506, 6th Street, Brooklyn, NY 11215, USATel +1 718 780 5260Fax +1 718 780 3266Email bmb9005@nyp.orgAbstract: Allgrove syndrome or triple A (3A) syndrome is a multisystem disorder which classically involves the triad of esophageal achalasia, alacrima, and adrenal insufficiency due to adrenocorticotropin hormone insensitivity. It follows an autosomal recessive pattern of inheritance and is associated with mutations in the AAAS (achalasia–addisonianism–alacrima syndrome) gene. Since its first description in 1978, the knowledge on clinical and genetic characteristics has been expanding; however, the current literature is limited to case reports and case reviews. Early recognition of the syndrome is challenging, given the rarity of the condition and high phenotypic heterogeneity even among members of kin. The coordination of care for these patients requires a multidisciplinary team of specialists, including endocrinologists, neurologists, gastroenterologists, ophthalmologists, developmental specialists, dentists, geneticists, and surgeons. In this review, we aim to summarize the current recommendations for the diagnosis, management, and follow-up of patients with 3A syndrome.Keywords: AAA, guidelines, alacrima, achalasia, adrenal failure